Gambaran Efek Samping Obat Sitotoksik pada Pasien Kanker yang Menjalani Kemoterapi di RSUP Fatmawati Jakarta 2023 - Sinukaban, Satriani (Jurnal Farmasi Klinik Best Practice, 2024)
Cancer is a non-communicable disease which is characterized by uncontrolled cell division in the body. In 2022 in Indonesia, breast cancer will rank first at 16.2%, followed by lung cancer at 9.5%, then cervical cancer at 9%, colorectal cancer at 8.7%, liver cancer at 5.8%, and other cancers at 50.7%. One of the treatment methods in Patients suffering from cancer receive chemotherapy. Chemotherapy is a treatment using drugs that can inhibit or kill cancer cells which involves a combination of two or more drugs that are cytotoxic and can cause side effects in patients, which is usually called DRP (drug related problem). This research aims to find out the picture side effects of cytotoxic drugs in patients undergoing chemotherapy. This research was carried out using a descriptive retrospective method, using MESO pharmacist report data in the cancer center room and there were 38 patients who experienced side effects from cytostatic drugs. Of the 38 patients, the largest disease was ovarian cancer, 13 of them, the most frequently used therapy regimen was a combination of Paclitaxel and Carboplatin, 15, the most common side effect experienced by chemotherapy patients was dyspnea which occurred in 21 patients. And the antidote that is often used is Dexamethasone injection in 27 cases.